Gestión del talento humano y desempeño laboral en la Droguería Roan Iquitos 2024 - Vergara Grandez, Jorge Jesus Martin (2025)
This study verified how human talent management influences job performance within Droguería Roan, located in Iquitos, in 2024. Using a quantitative technique and a non-experimental design, the relationship between these two variables was observed and examined at a specific point in time without any direct intervention. The research was based on structured surveys to collect data, and the instruments used proved to be highly reliable. Specifically, the reliability assessed through Cronbach’s Alpha was 0.963 for human talent management and 0.927 for job performance, reflecting a high internal consistency in the items used. When analyzing the results, it was found that the items of both instruments are highly related to each other, suggesting that they measure similar aspects. This was demonstrated by using Spearman’s correlation coefficient, which yielded a value of 0.695 with a significance level of 0.001, indicating a strong and statistically significant positive relationship between human talent management and job performance.